MANAJEMEN LAYANAN SISWA DI SEKOLAH MENENGAH PERTAMA (SMP) DI SMP MA’ARIF SINDANG AYU KECAMATAN CANDIPURO KABUPATEN LAMPUNG SELATAN - M. Ali Syaifuddin; An An Andari; Sugiran (UNISAN JURNAL, 2022)
This study aims to determine: (1) aspects of physical evidence (tangibles), (2) aspects of empathy (empathy), (3) aspects of reliability, (4) aspects of responsiveness (responsiveness), and (5) aspects of assurance ( assurance), in .The approach used in this research is a qualitative research with descriptive analysis type. Data from each dimension of service quality in this study were collected through interview, observation and documentation techniques. The research data were analyzed using triangulation technique. The results of the study prove that: (1) The quality of service aspects of physical evidence (tangible) is the availability of facilities and infrastructure that support learning, but library facilities and UKS rooms are not yet available. The Ma'arif Sindang Ayu Middle School continues to provide health services and reading room facilities by utilizing unused classrooms. (2) The quality of service in the empathy aspect is indicated by the concern for service users, in this case students, the attention to students who have below average ability levels. (3) The quality of service in the aspect of reliability is to provide services in accordance with what was promised, every information submitted is accurate and on target. (4) The service quality of the responsiveness aspect of the parties is shown by the willingness and ability of both criticism and suggestions. (5) Service quality assurance aspect (creating trust and providing assurance to customers that the level of success of the learning process at SMP Ma'arif Sindang Ayu Candipuro and the output is quite satisfactory.